2010
DOI: 10.1016/j.tra.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The smoothing effect of carpool lanes on freeway bottlenecks

Abstract: Real data show that reserving a lane for carpools on congested freeways induces a smoothing effect that is characterized by significantly higher bottleneck discharge flows (capacities) in adjacent lanes. The effect arises because disruptive vehicle lane changing diminishes in the presence of a carpool lane. The effect is reproducible across days and freeway sites: it was observed, without exception, in all cases tested.Queueing analysis shows that the effect greatly reduces the times spent by people and vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Later studies focused on the effects of BRT systems on both cars and buses (i.e, Shalaby, 1999;Japson & Ferreira, 2000;Currie et al, 2007;Arasan & Vedagiri, 2010;Cassidy et al, 2010). Using various methods (such as simulation or theoretical evaluation), these studies often conclude that it is difficult to justify the implementation of BRT systems if the effects on car traffic are also considered.…”
Section: Bus Priority Strategies Targeted To Linksmentioning
confidence: 99%
See 1 more Smart Citation
“…Later studies focused on the effects of BRT systems on both cars and buses (i.e, Shalaby, 1999;Japson & Ferreira, 2000;Currie et al, 2007;Arasan & Vedagiri, 2010;Cassidy et al, 2010). Using various methods (such as simulation or theoretical evaluation), these studies often conclude that it is difficult to justify the implementation of BRT systems if the effects on car traffic are also considered.…”
Section: Bus Priority Strategies Targeted To Linksmentioning
confidence: 99%
“…The authors determined that for cars to remain operating at an acceptable level of service (C), a volume to capacity ratio of approximately 0.55 and a road space allocation of 34% (for a 3 lane roadway) for buses would be needed. Finally, theoretical analysis conducted in Cassidy et al (2010) showed that it is possible to reduce total VHT by segregating bus and car traffic on circular beltways when the smoothing effect is considered. However the analysis assumed that bus demand is fairly high and was further idealized in that it ignored many complications of real-world traffic such as driver behaviour.…”
Section: Bus Priority Strategies Targeted To Linksmentioning
confidence: 99%
“…This factor also depends on the number of remaining free lanes: the higher the number of lanes, the smaller the overall effect (i.e., the higher the ). Merging effects and the impact of lane changes have been studied in freeway environments, either with an endogenous model [43][44][45], simulation [46,47], or empirical data [48,49]. In this paper, as it will be later shown, the parameter can be easily calibrated with a simple simulation experiment performed in a controlled manner.…”
Section: Formulationsmentioning
confidence: 99%
“…Cassidy et al . revealed smoothing effects, that is, favorable influences of carpool lane on the whole traffic flows. In addition, Patire and Cassidy observed that lane‐changing maneuvers induced by periodical speed disturbances mainly resulted in outflow reductions in uphill freeway segments.…”
Section: Related Workmentioning
confidence: 99%